Progress in Global Surgery; Comment on "Global Surgery - Informing National Strategies for Scaling Up Surgery in Sub-Saharan Africa" - Haile T. Debas (Kerman University of Medical Sciences, 2018)
Impressive progress has been made in global surgery in the past 10 years, and now serious and evidence-based national strategies are being developed for scaling-up surgical services in sub-Saharan Africa. Key to achieving this goal requires developing a realistic country-based estimate of burden of surgical disease, developing an accurate estimate of existing need, developing methods, rigorously planning and implementing the plan, and scaling-up essential surgical services at the national level.